Reliability and Validity of the Modified Version of Children’s Fear Survey Schedule-dental Subscale in 9-12 Years Old Schoolchildren in Bosnia and Herzegovina - Bajric, Elmedin (Med Arch, 2018)
BACKGROUND: Dental fear and anxiety (DFA) are present worldwide globally, as well as in children. These psychological clinical entities in its progressive phase lead to avoiding of dentists and dental appointments, and consequtive impairments of oral health. If we ignore these facts, we would have the strenghtening of this relationship in a way of further oral health impairments and lost of dental hard and soft tissues, as well as appearance of dental phobia as the most negative form of psychological reaction to dental stimuli. Original CFSS-DS scale and its modifications, as the most used instruments for evaluation of DFA presence so far, showed various disadvantages. These were the reasons why we wanted to design new psychometric instrument for better evaluation of DFA presence in children compared to evaluation which the existed scales could offer nowadays, in a form of the Modified Version of CFSS-DS scale (CFSS-DS-mod scale). MATERIALS AND METHODS: There were 809 schoolchildren from 8 cities of Bosnia and Herzegovina aged 9-12 years that participated in the study. There was one school per city where the schoolchildren answered to the questions from the CFSS-DS-mod scale. RESULTS: 636 schoolchildren correctly answered to the scale questions. The CFSS-DS-mod scale showed excellent internal consistency reliability values (with Cronbach α>0.9), and also validity results (mostly over 60% of explained variance of obtained results) with two-dimensional concept of DFA presence. CONCLUSION: The CFSS-DS-mod scale represents good psychometric instrument for evaluation of the DFA presence in 9-12 year old schoolchildren in Bosnia and Herzegovina. Some of normative values of this psychometric instrument should be determined, in order to expand its usage in children.